The Role of Mudharabah Financing in The Development of The Small and Medium Enterprise Sector - Suci Ralita Lestari; Melati Sihombing; Jelita Br Simangunsong; Indah Setiarini; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
In sharia economics, mudharabah is a common type of contract or commercial arrangement that relies on collaboration between management and capital. Individuals or corporate organizations from different sectors of the economy operate SMEs, which are community-centric and highly affordable autonomous manufacturing business units. In accordance with current norms and conditions, the purpose of this study is to find out the impact of mudharabah funding on the SME sector. Descriptive analysis is a methodology used in research to examine data from reliable sources, including Central Statistics Agency statistics, publications, journals, and websites. The findings of the study show that the purpose of Mudharabah funding is to assist SMEs in their commercial operations. In addition, this mudharabah financing may provide people with a place to direct their extra money to more useful uses. Then SMEs are expected to be more helpful in financing mudharabah for members of micro, small and medium entrepreneurs so that the business they run becomes better and develops so that the welfare of their families is also better and harmonious.